Pengaruh Pendidikan dan Pelatihan Terhadap Peningkatan Kualitas SDM Bank Syariah Pada Bank Syariah Mandiri KCP Lamongan - Pratiwi, Shonia Lingga; Cahyono, Hendry (Jurnal Ekonomika dan Bisnis Islam, 2018)
This study aims to determine how the influence of variables between education and training on improvement of the quality of human resources of sharia banks in lamongan. This research is a quantitative approach. Methods of data collection using questionnaires distributed to respondents. The number of respondents in this study were 17 employees. Data analysis using path analysis model, classical assumption test and hypothesis test. These results indicate that education and training simultaneously have a significant effect on the quality of human resources, partially only training variables that have a significant impact on improving the quality of human resources. The amount of influence of education and training on improving the quality of human resources is 87.6% and the remaining 12.4% is influenced by other variables that are not included in the research variables